Factors influenced of drug-resistant tuberculosis and non-drug-resistant tuberculosis patients in Pulmonary Hospital Dr. M. Goenawan Partowidigdo, Bogor district - Cicilia Windiyaningsih; Hendra Badaruddin (Tarumanagara Medical Journal, 2021)
Tuberculosis is one cause of death, the ninth of all diseases in the world. The increasing cases of antimicrobial-resistant tuberculosis is a global challenge especially multi-drug resistant TB (MDR-TB). Drug-resistant Tuberculosis is classified as a condition where Mycobacterium tuberculosis can’t be treated with anti-tuberculosis drugs. The study aimed to determine the associated risk factors with drug-resistant Tuberculosis compared with second category tuberculosis (non-drug resistant Tuberculosis). A case-control study was undertaken — there were 40 cases (drug-resistant TB) and 80 controls (non-drug resistant TB) were conveniently sampled. Data we collected from medical records and direct interviews using questionnaires. The variables of interest were gender, age, occupation, income, medication history, side effects, regularity of taking medication, nutritional status, smoking, alcohol, contact history, treatment chronology, and health facility distance.  The results showed majority of respondents were mostly men, age >41 years, low education, work, incomes >1.00,000 IDR, failed/discontinued treatment, no side effects, adherence treatment, BMI> 18.5, no smoking, no alcohol consumption, no contact history, lack of knowledge, drug swallowing supervisor (DSS), health services distance <3 km.  Final model adherence of treatment p-value 0.0001, OR 6.460, 95% CI 2.384-17.504; contact history p-value 0.004, OR 4.549, 95% CI 1.623-12.748; side effects p-value 0.017, OR 3.580, 95% CI 1.260-10.17; health service distance p-value 0.061, OR 2.627, 95% CI 0.955-7.226. These four factors have contributed to the occurrence of drug-resistance TB.